The Influence of Principal Leadership on School Improvement in a Philippine Public Secondary School: A Qualitative Study - Kenneth Panga; Cherrynel P. Bohayo; Erica Oquialda; Margie K. Tabayag; Jan Blademir Bradecina (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study investigates the influence of a school principal’s leadership on school improvement in a public secondary school in Camarines Sur, Philippines. Employing a qualitative design, the researchers conducted in-depth interviews with the school principal and four teachers, and analyzed the data using a thematic analysis approach. The principal demonstrated a hands-on leadership style by fostering collaboration, mentoring staff, promoting instructional effectiveness, and strengthening school-community relationships. Teachers described the principal as proactive, approachable, and committed to shared goals. The school faced persistent challenges, including limited financial resources, insufficient instructional materials, high staff workload, and inconsistent stakeholder participation. To address these, the principal implemented strategies such as participatory planning, open communication channels, professional development initiatives, and inclusive decision-making processes. These actions enhanced teamwork and adaptability within the school. The study highlights the importance of strategic, collaborative, and responsive leadership in overcoming barriers and sustaining school progress within the context of Philippine public education.